Clinical Types and associated maternal factors of Attention Deficit /Hyperactivity Disorder ADHD in a group of children in Baghdad - Younis, Maha S.; Sadiq, Basim D.; Al-Saiddy, Abbas M. (Journal of the Faculty of Medicine Baghdad, 2014)
Fac Med Baghdad 2014; Vol.56, No.2 Received: Feb., 2014 Accepted April. 2014 Background: Attention Deficit Hyperactivity Disorder (ADHD) is a common neurobehavioral disorders in children includes pervasive inattention, over activity, and impulsivity imposing psychological and cognitive impairment. Objectives: This study aims to examine the clinical types and the association of some maternal risk factors and developmental milestone with ADHD among a group of school-age children. Method: 100 primary school- age children affected with ADHD of both sexes were clinically assessed by the semi-structured interview questionnaire of ADHD (SSIQ) according to (DSM-IV-TR) during April-August 2013at Ibn-Rushd Psychiatric Teaching Hospital in Baghdad results were submitted to statistical analysis. Results: Most of the children were urban males with average age of 8 years old presented with combined type of ADHD and had a normal developmental milestone. Maternal adversities were not insignificantly associated. Conclusion: ADHD was presented mostly in its combined form. Maternal adversities and type of labor was not significantly associated with its morbidity. The authors call for improvement child’s mental health services.